A Critical & Modern Practical Study of the Elements of God Attainment Science In Worldwide Religions: Exploring the Paradoxes of God Attainment in Worldwide Religions (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Sanskrit wordbija means the seed and cause of this whole universe. The understanding thateverything manifested is contained in a single seed is reached in higher statesof consciousness, Samadhi. Shakti is also spanda the creative pulsation ofShiva, the foundational consciousness, motion-less movement. The movements,vibration and pulsation of spanda are only apparent – the temporal appearancesof illusory forms emanating from the eternal motion-less stillness that is theOne. The manifest is simultaneously un-manifest, because the Oneness is neveraffected or changed by the appearance of the universe. These contradictions areuseful and challenge us to alter our conditioned linear thinking. The path Homeis sometimes bewildering and often presenting the chicken or the egg puzzle –which comes first? Are our ‘achievements’ the result of our own endeavors, orare they merely God’s grace? Is our heartfelt devotion for God a result of ourown will, or is it the will of God that immerses us in such feelings.